Penguatan Karakter Keagamaan Berbasis Budaya Sekolah di SMP Raudlatul Muta’allimin Babat Lamongan - Ikmal, Hepi; Al-Haidar, M Dzulham Yusuf (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2024)
Strengthening religious character has an important role in the era of disruption, but currently the increasingly sophisticated technology and the development of science have given rise to positive and negative impacts. This study discusses the strengthening of religious character and supporting and inhibiting factors for strengthening religious character based on school culture at SMP Raudlatul Muta'allimin Babat Lamongan. This study uses a qualitative case study approach. Data collection uses observation, interview and documentation methods. The results of the study show that strengthening religious character at SMP Raudlatul Muta'allimin is carried out through routine habits with several activities, namely religious and non-religious activities, including: praying, reading the Qur'an, studying Islamic boarding school books, praying in congregation, istighotsah tahlil manaqib, carrying out ceremonies and scouts, mutual respect and tolerance. The supporting factors include: a pesantren-style environment, school regulations, accompanying teachers/mentors, religious guidebooks, religious and non-religious activities. While the inhibiting factors for strengthening religious character are lack of student awareness, lack of teacher supervision and competence, lack of facilities and infrastructure.